Growth performance and biomass production of Eleusine indica and Rorippa sylvestris on heavy metal contaminated soil after biochar application - Rossyda Priyadarshini; Amir Hamzah; A Astuti (Brawijaya University, 2020)
Heavy metal contamination was an environmental and human health problem all over the world. Cadmium is the most hazardous heavy metals due to its high mobility and toxicity at low concentrations. Lead (Pb) also belongs to the hazard element caused by its prolonged persistence in the soil. This study aimed to develop the remediation techniques on polluted land, i.e. a combination of biochar and indigenous plant. The biochar was produced by slow pyrolysis method. This experiment was conducted at the farmland at Sumber Brantas, Malang, East Java. We used rice husk and tobacco waste biochar, and Eleusine indica (L.) Gaertn and Rorippa sylvestris (L.) Bess. as remediator plants. The results showed that rice husk biochar had a significant effect on pH value and potassium content (p = 0.0001; p=0.0004). On the contrary, the soil nitrogen content, soil organic-C content, and soil cation exchange capacity applied with tobacco waste biochar application were higher than that applied with rice husk biochar (p = 0.03; p=0.00001; p = 0.00001). The improvement of soil characteristics increased the growth of Eleusine indica and Rorippa sylvestris as indicated by the plant height and biomass. The addition of biochar could promote the growth of remediator plant and enhanced the accumulation of Pb and Cd in the plants. Mixtures of rice husk biochar and tobacco waste biochar caused Eleusine indica more effectively absorbed heavy metals than Rorippa sylvestris on all types of biochar treatments; Eleusine indica absorbed Pb and Cd higher than Rorippa sylvestris as shown by Pb and Cd contents in the soil.